2010
DOI: 10.1161/circulationaha.110.964619
|View full text |Cite
|
Sign up to set email alerts
|

β 3 Adrenergic Stimulation of the Cardiac Na + -K + Pump by Reversal of an Inhibitory Oxidative Modification

Abstract: Background-Inhibition of L-type Ca 2ϩ current contributes to negative inotropy of ␤ 3 adrenergic receptor (␤ 3 AR) activation, but effects on other determinants of excitation-contraction coupling are not known. Of these, the Na ϩ -K ϩ pump is of particular interest because of adverse effects attributed to high cardiac myocyte Na ϩ levels and upregulation of the ␤ 3 AR in heart failure. Methods and Results-We voltage clamped rabbit ventricular myocytes and identified electrogenic Na ϩ -K ϩ pump current (I p ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 36 publications
8
92
0
Order By: Relevance
“…This increase in pump current was abolished by L‐ N G ‐nitroarginine methyl ester, showing that stimulation was mediated by eNOS‐derived NO production enhanced by ex vivo supplementation of BH 4 . In previous reports we have shown that NO generation from eNOS stimulates the Na + ‐K + pump,10, 38 and conditions that cause eNOS uncoupling inhibit the Na + ‐K + pump 24, 3940 where changes in redox milieu are sensed by eNOS and transduced to regulation of the Na + ‐K + pump function via redox‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This increase in pump current was abolished by L‐ N G ‐nitroarginine methyl ester, showing that stimulation was mediated by eNOS‐derived NO production enhanced by ex vivo supplementation of BH 4 . In previous reports we have shown that NO generation from eNOS stimulates the Na + ‐K + pump,10, 38 and conditions that cause eNOS uncoupling inhibit the Na + ‐K + pump 24, 3940 where changes in redox milieu are sensed by eNOS and transduced to regulation of the Na + ‐K + pump function via redox‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…To detect glutathionylation of eNOS and β 1 Na + ‐K + pump subunit in co‐immunoprecipitation experiments, an antibody against glutathionylated protein (anti‐glutathione antibody) was used to detect glutathionylation 10. Aorta was homogenized in ice‐cold lysis buffer containing 150 mmol/L NaCl, 50 mmol/L Tris‐HCl (pH 8.0), 1% Triton X‐100, 2 mmol/L EDTA, and protease inhibitor (Complete EGTA‐free, Roche Diagnostics), followed by centrifugation at 16 000 g for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations